CONCEPT OF COSTS AND APPROACHES TO THEIR CLASSIFICATION - Jumaniyazov Iskandar Bakhodirovich, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
The article examines the concept of costs and approaches to their classification. The definitions and approaches of foreign and domestic economists to the concept of costs and their classification are studied. The author's approach to the concept of costs is given, a conclusion on their classification is formed and proposals are developed.